A method for analyzing ultra-low acid-soluble aluminum in cord steel ping-pong samples
By annealing the cord steel and optimizing the dissolution process, combined with inductively coupled plasma atomic emission spectrometry, the accuracy and cost issues of detecting ultra-low acid dissolved aluminum in cord steel have been solved, achieving high-precision, low-cost, and environmentally friendly detection results.
Patent Information
- Application Number
- CN202411259103.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-10
AI Technical Summary
Existing technologies cannot effectively detect the content of ultra-low acid-soluble aluminum in steel cord, resulting in unstable test results, high costs, and environmental pollution risks.
Annealing was used to remove the surface oxide layer. The sample was dissolved in dilute nitric acid and dilute hydrochloric acid. The sample was then analyzed using inductively coupled plasma atomic emission spectrometry (ICP-AES). Optimized analytical parameters were set, high-purity iron was used as the reference component, and the 396.152 nm spectral line was selected for detection.
It enables accurate detection of ultra-low acid-soluble aluminum content in tire cord steel, reduces analysis costs, and produces no environmental pollution. The test results are stable and precise.
Smart Images

Figure CN118777016B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steel analysis, and in particular to a method for analyzing ultra-low acid-soluble aluminum in a cord steel ping-pong sample. Background Art
[0002] The inclusion content of cord steel has remained high for a long time. Through the analysis of excessive inclusions in wire rods, it was found that the types of excessive inclusions are mainly SiO2-CaO-Al2O3, among which the Al2O3 component content is only about 5%, which makes the inclusions deviate from the low melting point area of SiO2-CaO-Al2O3 inclusions; if the Al2O3 content can be increased to 15-20%, the low melting point of SiO2-CaO-Al2O3 inclusions can be reduced, and the deformability of cord steel can be significantly improved. If the Al2O3 content of inclusions in molten steel is to be increased, the acid-soluble aluminum content in molten steel needs to be controlled; research shows that if the acid-soluble aluminum content is controlled at 3-6ppm, the Al2O3 component content in SiO2-CaO-Al2O3 inclusions in cord steel can be increased to 15-20%. In order to accurately control the inclusion components of cord steel, it is necessary to accurately detect the acid-soluble aluminum.
[0003] Aluminum exists in steel mainly in the form of metal solid solution, and a small part exists in the form of aluminum oxide and aluminum nitride; metal aluminum, aluminum nitride and aluminum sulfide are generally soluble in acid, which is called acid-soluble aluminum. It is beneficial to refine the grain within a certain range and improve the performance of steel. However, aluminum oxide and spinel are often insoluble in acid, which is called acid-insoluble aluminum; acid-insoluble aluminum reduces the purity of steel, which in turn leads to reduced physical and mechanical properties of steel.
[0004] The analysis of acid-soluble aluminum at home and abroad mainly adopts inductively coupled plasma atomic emission spectrometry, spark source atomic emission spectrometry and wet manual method. Among them, the existing national standard of inductively coupled plasma atomic emission spectrometry GB / T20125-2006 "Determination of multi-element content of low alloy steel Inductively coupled plasma atomic emission spectrometry" has an acid-soluble aluminum analysis range of 0.004~0.10%. Due to the introduction of background interference and acid effect problems, its repeatability r≥0.0007% and reproducibility R≥0.0023% are completely unsuitable for acid-soluble aluminum analysis in cord steel. GB / T 223.81-2007 "Determination of total aluminum and total boron content in steel and alloys - microwave digestion - inductively coupled plasma mass spectrometry" has a total aluminum analysis range of 0.0005%~0.10%, which is suitable for total aluminum determination; due to the low sample weight (0.1g), this method can only be used for inductively coupled plasma mass spectrometers. For high-carbon cord steel, increasing the sample weight for microwave digestion will lead to carbide refinement, which is easy to block the sample injection tube during analysis, resulting in unstable or erroneous analysis data. In addition, due to the high price of inductively coupled plasma mass spectrometers and the high requirements of the entire experimental process, most laboratories do not have them or find it difficult to implement. At present, other domestic and international literature on acid-soluble aluminum detection has not reported on the content ≤0.0010%. Summary of the invention
[0005] The present invention aims to provide an analysis method for ultra-low acid-soluble aluminum in a cord steel ping-pong sample, which can be used for detecting acid-soluble aluminum with a content of 0.0002% to 0.04% in cord steel, thereby solving the problem that there is no analysis method for ultra-low acid-soluble aluminum in steel. The method has the characteristics of high accuracy, low analysis cost and no environmental pollution, and is conducive to promotion and application.
[0006] To achieve the above object, the present invention proposes the following technical solutions:
[0007] In the first aspect, a method for analyzing ultra-low acid-soluble aluminum in a cord steel ping-pong sample is proposed, comprising the following steps:
[0008] 1) Annealing the cord steel ping-pong sample and removing the surface oxide layer after the sample is cooled to obtain a pre-treated sample;
[0009] 2) Drill the pretreated sample, wash and dry the cuttings in anhydrous ethanol and use them as test samples;
[0010] 3) Weigh the test sample, first dissolve the test sample with dilute nitric acid until the reaction is stable, then add dilute hydrochloric acid to dissolve the test sample under heating conditions, and then add deionized water intermittently during the dissolution process until the test sample is completely dissolved to obtain a reaction solution;
[0011] 4) Using medium-speed quantitative filter paper to perform hot filtration on the reaction solution, and using acid washing on the filter paper to obtain a test solution containing all the acid-soluble aluminum in the test sample;
[0012] 5) Prepare a 100µg / mL aluminum standard solution using pure aluminum and hydrochloric acid as reactants; use high-purity iron as a reference component and adopt the same dissolution steps as the test sample to obtain an iron solution; wherein the mass fraction of aluminum in pure aluminum is not less than 99.99%, and the mass fraction of iron in high-purity iron is not less than 99.98%;
[0013] 6) Using the iron solution as a blank solution, different concentrations of acid-soluble aluminum standard solutions were prepared by adding different volumes of aluminum standard solutions; wherein the volume of aluminum standard solution added to any acid-soluble aluminum standard solution did not exceed 2.00 mL;
[0014] 7) Using an inductively coupled plasma emission spectrometer, analyze the acid-soluble aluminum standard solution under set analysis parameters to obtain an acid-soluble aluminum calibration curve; wherein the correlation coefficient of the acid-soluble aluminum calibration curve is not less than 0.9999;
[0015] 8) Determine the acid-soluble aluminum content in the test solution based on the acid-soluble aluminum calibration curve.
[0016] Furthermore, the analysis parameters in step 7) are set as follows: RF power 1150 W, nebulizer flow rate 0.50 L / min, pressure 2.10-2.30 bar, auxiliary gas flow rate 0.50 L / min, cooling gas flow rate 12.5 L / min, analysis pump speed 45 rpm, analysis spectrum line 396.152 nm, left background subtraction point 396.13 nm, right background subtraction point 396.17 nm.
[0017] Furthermore, the lower limit of detection of the acid-soluble aluminum content in the analytical method at the analytical spectrum line of 396.152 nm is 0.00015%.
[0018] Furthermore, the specific process of step 3) is as follows:
[0019] Weigh the test sample into a steel volumetric flask, add dilute nitric acid to it and react for 3-5 minutes, then add dilute hydrochloric acid to mix, and dissolve the test sample under heating conditions of 200-300°C; add deionized water for the first time when bubbles appear on the surface of the reaction liquid, continue heating until bubbles appear on the surface of the reaction liquid, add deionized water for the second time, continue heating until bubbles appear on the surface of the reaction liquid, add deionized water for the third time, finally heat until bubbles appear on the surface of the reaction liquid and the test sample is completely dissolved, then cool to obtain a reaction solution.
[0020] Furthermore, the annealing process in step 1) is: heating the cord steel ping-pong sample in a heating furnace at 800° C. to 950° C. for 2 h to 4 h.
[0021] Furthermore, the thickness of the surface oxide layer removed in step 1) is not less than 1 mm.
[0022] Furthermore, in step 3), the dilute nitric acid is prepared by mixing nitric acid and deionized water in a volume ratio of 1:1, and the dilute hydrochloric acid is prepared by mixing hydrochloric acid and deionized water in a volume ratio of 1:1, and both nitric acid and hydrochloric acid are selected from reagents of premium purity or above.
[0023] Furthermore, the resistivity of the deionized water is not less than 18 MΩ·cm.
[0024] Furthermore, the mass of the test sample used for the determination of the mass fraction of acid-soluble aluminum in the analytical method is not less than 2.0 g, and the total mass of the test sample used for the repeatability test is not less than 6.0 g.
[0025] Furthermore, the content of acid-soluble aluminum in the cord steel determined by the analytical method is 0.0002% to 0.04%.
[0026] It can be seen from the above technical solutions that the technical solutions of the present invention have the following beneficial effects:
[0027] The present invention discloses an ultra-low acid-soluble aluminum analysis method in a cord steel ping-pong sample, comprising the following steps: 1) annealing the cord steel ping-pong sample, and removing the surface oxide layer after the sample is cooled to obtain a pre-treated sample; 2) drilling the pre-treated sample, washing the cuttings in anhydrous ethanol, and drying them as test samples; 3) weighing the test sample, first dissolving the test sample with dilute nitric acid until the reaction is stable, then adding dilute hydrochloric acid to dissolve the test sample under heating conditions, and then intermittently adding deionized water during the sample dissolution process until the test sample is completely dissolved to obtain a reaction solution; 4) hot filtering the reaction solution with medium-speed quantitative filter paper, and filtering the filter paper with water. Acid washing is performed to obtain a test solution in which all the acid-soluble aluminum in the test sample is dissolved; 5) pure aluminum and hydrochloric acid are used as reactants to prepare an aluminum standard solution with a concentration of 100µg / mL; high-purity iron is used as a reference component, and the same dissolution steps as the test sample are used to obtain an iron solution; 6) the iron solution is used as a blank solution, and acid-soluble aluminum standard solutions of different concentrations are prepared by adding different volumes of aluminum standard solutions; 7) an inductively coupled plasma emission spectrometer is used to analyze the acid-soluble aluminum standard solution under set analysis parameters to obtain an acid-soluble aluminum calibration curve; 8) according to the acid-soluble aluminum calibration curve, the acid-soluble aluminum content in the test solution is determined. The present invention proposes a method for analyzing ultra-low acid-soluble aluminum in steel, which not only has high accuracy and low analysis cost, but also has the characteristics of no environmental pollution and can be promoted and applied.
[0028] In addition, the beneficial effects of the method for analyzing ultra-low acid-soluble aluminum in cord steel ping-pong samples disclosed in the present invention are:
[0029] 1) The cord steel is high carbon steel, and the ping-pong samples taken from it are often accompanied by physical defects such as shrinkage cavities and hollows, which lead to certain segregation phenomena; in addition, it is high carbon steel with high hardness, and the drill bit is easy to break or wear out quickly during the drilling process; by properly annealing the cord steel ping-pong samples, the crystal structure can be refined, the structural inhomogeneity can be eliminated, and the sample analysis results can be more representative; at the same time, the sample hardness can be reduced, the plasticity can be improved, the wear of the drill bit and the pollution that may be introduced by its wear can be reduced, and the uniformity and representativeness of the analysis sample can be further improved; after annealing, the sample is milled to remove the surface oxide layer to prevent the surface pollution that may be introduced by removing the oxide layer with abrasive belts or sandpaper.
[0030] 2) The sample is dissolved in dilute nitric acid until the reaction is stable and then dilute hydrochloric acid is added to dissolve the sample. Deionized water is added intermittently during the dissolution process to refine the carbides in the sample and prevent inclusions during the filtration process. At the same time, medium-speed quantitative filter paper hot filtration and acid washing are used to further reduce possible inclusions and improve the stability and accuracy of the ultra-low acid-soluble aluminum content test results.
[0031] 3) The blank solution of the acid-soluble aluminum calibration curve uses high-purity iron to accurately simulate the matrix iron content in the cord steel. The blank solution with high-purity iron as the base and the same sample processing method is used as the zero standard to reduce the impact of the small difference between the curve and the sample matrix, and further improve the detection precision of ultra-low acid-soluble aluminum.
[0032] 4) Selecting the 396.152 nm analysis line, which has the best detection limit of 0.00015% and stability under the analysis method disclosed in the present invention, is completely suitable for the detection of ultra-low acid-soluble aluminum in cord steel.
[0033] It should be appreciated that all combinations of the foregoing concepts, as well as additional concepts described in greater detail below, may be considered to be part of the inventive subject matter of the present disclosure, provided such concepts are not mutually inconsistent.
[0034] The foregoing and other aspects, embodiments and features of the present invention can be more fully understood from the following description in conjunction with the accompanying drawings. Other additional aspects of the present invention, such as the features and / or beneficial effects of the exemplary embodiments, will be apparent from the following description or learned from the practice of the specific embodiments according to the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The accompanying drawings are not drawn to scale according to actual reference objects. In the accompanying drawings, each identical or nearly identical component shown in various figures may be represented by the same reference numeral. For the sake of clarity, not every component is labeled in each figure. Now, embodiments of various aspects of the present invention will be described by way of example and with reference to the accompanying drawings, in which:
[0036] Figure 1The figure is a calibration curve of acid-soluble aluminum prepared according to the acid-soluble aluminum standard solution in the embodiment;
[0037] Figure 2 This is the spectrum peak diagram of the acid-soluble aluminum standard solution prepared in Example at the analytical spectrum line of 396.152nm. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meaning understood by people with general skills in the field to which the present invention belongs.
[0039] The words "first", "second" and similar words used in the patent application specification and claims of the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. Similarly, unless the context clearly indicates otherwise, the singular form of "a", "an" or "the" and other similar words do not indicate a quantitative limitation, but indicate the existence of at least one. "Include" or "comprises" and other similar words mean that the elements or objects appearing before "include" or "comprises" include the features, wholes, steps, operations, elements and / or components listed after "include" or "comprises", and do not exclude the existence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections.
[0040] The aluminum content determination method disclosed in the national standard GB / T20125-2006 "Determination of multi-element content of low alloy steel by inductively coupled plasma atomic emission spectrometry" is as follows: weigh 0.5g of sample in a 200mL beaker, add 10mL of water and 5mL of nitric acid, cover with a watch glass, slowly heat until bubbling stops, then add 5mL of hydrochloric acid, and continue to heat until completely decomposed; for samples containing insoluble carbides, add 5mL of perchloric acid, emit perchloric acid smoke, cool, then add water, 5mL of nitric acid, and 5mL of hydrochloric acid to dissolve the salts and make a fixed volume determination; since cord steel is high-carbon steel, perchloric acid must be added for fuming in accordance with this standard. The perchloric acid in the analysis process is a high-concentration acid. In addition to introducing background interference itself, the inconsistency of its fuming degree causes the amount of residual test solution to be inconsistent. Therefore, its influence cannot be reduced or deducted by the same operation of the curve and the sample. At the same time, the overall acidity is ≥10%, and the influence of the acid effect on the ultra-low content determination cannot be ignored. Therefore, the repeatability of acid-soluble aluminum in this method is r≥0.0007%, and the reproducibility is R≥0.0023%, which makes it completely unsuitable for the analysis of acid-soluble aluminum in cord steel.
[0041] The national standard GB / T 223.81-2007 "Determination of total aluminum and total boron content in steel and alloys by microwave digestion-inductively coupled plasma mass spectrometry" has the following process for the determination of total aluminum: 3mL hydrochloric acid and 1mL nitric acid are used to dissolve the sample, and after a violent reaction, 1mL hydrofluoric acid is added to the microwave digestion instrument to digest the sample; the method requires the use of microwave digestion equipment, and the introduction of hydrofluoric acid, which is highly polluting to the environment, can only be used for total aluminum analysis and determination, and cannot meet the requirements for acid-soluble aluminum detection in cord steel. In addition, due to the low sample weight (0.1g), this method can only be used for inductively coupled plasma mass spectrometry. If the sample weight is increased for high-carbon cord steel, microwave digestion will lead to carbide refinement, which is easy to block the sample inlet tube during analysis, resulting in unstable or erroneous analysis data. In addition, due to the high price of inductively coupled plasma mass spectrometers and the high requirements of the entire experimental process, most laboratories do not have them or it is difficult to implement. In addition, other domestic and international literature on acid-soluble aluminum detection has not reported on ≤0.0010%.
[0042] Therefore, the present invention aims to propose a method for analyzing ultra-low acid-soluble aluminum in cord steel ping-pong samples, so as to solve the technical problem of the lack of an analysis method for ultra-low acid-soluble aluminum in steel in the prior art.
[0043] The method for analyzing ultra-low acid-soluble aluminum in cord steel ping-pong samples disclosed in the present invention will be further specifically introduced below in conjunction with the specific embodiments shown in the accompanying drawings.
[0044] Example 1
[0045] Step 1) placing the cord steel ping-pong sample in a heating furnace, heating it at 800°C-950°C for 3 hours and then cooling it with the furnace;
[0046] After cooling, the surface oxide layer of the sample is removed on a milling machine with a thickness of not less than 1 mm to obtain a pretreated sample.
[0047] Step 2) Drill the pretreated sample on a drilling machine, wash and dry the chip sample in anhydrous ethanol and use it as the test sample. The mass of the chip sample is not less than 2.0g. In addition, the total mass of the chip sample of the test sample used for the repeatability test is not less than 6.0g, and the number of repeatability tests is not less than 6 times.
[0048] Step 3) Weigh 0.5 g of the test sample into a 100 mL steel volumetric flask, add 5 mL of dilute nitric acid, react for 3 to 5 minutes, add 10 to 15 mL of dilute hydrochloric acid, mix well, and heat on a hot plate or electric furnace at 200° C. to dissolve the sample; when bubbles appear on the surface of the reaction solution, add 5 to 10 mL of deionized water for the first time, continue heating until bubbles appear on the surface of the reaction solution, add 3 to 5 mL of deionized water for the second time, continue heating until bubbles appear on the surface of the reaction solution, add 3 to 5 mL of deionized water for the third time, and finally heat until bubbles appear on the surface of the reaction solution and the test sample is completely dissolved, then cool to obtain a reaction solution; wherein, the dilute nitric acid is prepared by nitric acid and deionized water in a volume ratio of 1:1, the dilute hydrochloric acid is prepared by hydrochloric acid and deionized water in a volume ratio of 1:1, and the nitric acid and the hydrochloric acid are both selected from reagents of superior purity or above;
[0049] Step 4) The reaction solution is hot filtered through medium-speed quantitative filter paper into a 100 mL volumetric flask, and the filter paper is washed with dilute hydrochloric acid prepared by mixing super-pure or higher purity hydrochloric acid with deionized water at a ratio of 1:99 to 1:95. The washing is stopped when the filtrate reaches 80 to 90 mL. After cooling to room temperature, the volume is adjusted to 100 mL with the dilute hydrochloric acid to obtain a test solution in which all the acid-soluble aluminum in the test sample is dissolved.
[0050] Step 5) Weigh 1.0000g of pure aluminum with a mass fraction of ≥99.99%, place it in a 500mL beaker, add 50mL of dilute hydrochloric acid prepared by mixing super-pure or higher purity hydrochloric acid with deionized water in a ratio of 1:1, cover with a watch glass, dissolve completely at low temperature, cool to room temperature, and make up to volume in a 1000mL volumetric flask; then transfer 10.00mL of the made-up solution to a 100mL volumetric flask, add 10mL of the hydrochloric acid, dilute to the mark with deionized water, mix well and set aside to prepare a standard aluminum solution with a concentration of 100µg / mL.
[0051] Step 6) Weigh 0.490 g of high-purity iron with a mass fraction of ≥ 99.98% and dissolve it in 1# to 6# steel volumetric flasks according to step 3) to obtain an iron solution;
[0052] Step 7) According to Table 1 below, different volumes of the aluminum standard solution in step 5) are transferred to 1#~6# steel volumetric flasks filled with iron solution to prepare acid-soluble aluminum standard solutions of different concentrations;
[0053] Table 1 Proportions of standard acid-soluble aluminum solutions
[0054]
[0055] Prepare the acid-soluble aluminum standard solution. The volume of the aluminum standard solution pipetted should be controlled within the range of 0.00mL~2.00mL. For example, when the sample weight is 1.0g, 20.00mL of the solution pipetted in step 5) is fixed to a 100mL volumetric flask and the concentration is maintained at 200µg / mL, thereby ensuring that the volume of the aluminum standard solution pipetted in step 7) is within the range of 0.00mL~2.00mL.
[0056] Step 8) Using an inductively coupled plasma emission spectrometer, the acid-soluble aluminum standard solutions in Table 1 are sequentially absorbed into the spectrometer under set analysis parameters to obtain Figure 1 The acid soluble aluminum calibration curve shown and Figure 2 The peak spectrum of the acid-soluble aluminum standard solution at the analytical spectrum line of 396.152nm is shown; wherein, the model of the inductively coupled plasma emission spectrometer is iCAPPRO XP Duo, and the analysis parameters are: RF power 1150W, nebulizer flow rate 0.50L / min, pressure 2.10~2.30bar, auxiliary gas flow rate 0.50L / min, cooling gas flow rate 12.5 L / min, analysis pump speed 45rpm, and analysis spectrum line 396.152nm;
[0057] Step 9) The solution to be tested in step 4) is measured under the acid-soluble aluminum calibration curve obtained in step 8), and the result can be directly read after completion.
[0058] In the process steps of the above analysis method, the deionized water used is deionized water with a resistivity of not less than 18 MΩ·cm; the correlation coefficient of the acid-soluble aluminum calibration curve obtained in step 8) must be ≥0.9999, otherwise find the cause and re-establish the curve.
[0059] The process of determining the analysis line in step 8) above is as follows:
[0060] The standards related to inductively coupled plasma emission spectrometer for aluminum content analysis in steel, such as GB / T20125, YB / T4396, SN / T2718, etc., all recommend 394.401nm and 396.152nm as analytical spectral lines, and the Mo element spectral line may interfere with the aluminum 396.125nm. Studies have found that the secondary spectral line 396.150 of the Mo element will cause spectral overlap interference with the aluminum 396.152nm spectral line, but the Mo element is a secondary spectral line with a low relative intensity. It basically does not interfere when Mo≤0.05%, and the interference can be completely ignored when Mo≤0.01%. The inventors conducted 11 blank determinations on the two spectral lines under the analytical conditions of this method. The detection limit ( C L ) formula calculation, C L =( K*S b ) / M , confidence factor K =3, M is the slope of the calibration curve in the low concentration range, S b is the blank standard deviation, and the results are shown in Table 2 below.
[0061] Table 2 Spectral detection limits of the method
[0062]
[0063] The slope of the curve is ≥0.9999, which is calculated as 1 in the above formula. Generally, 3-5 times of the detection limit of the method is used as the credible value (lower detection limit). Therefore, the lower detection limit of the 394.401nm analysis line is 0.00009*5=0.00045%, and the lower detection limit of the 396.152nm analysis line is 0.00003*5=0.00015%. Therefore, this analysis method selects the 396.152nm analysis line to meet the detection requirements.
[0064] In addition, through further research on the analysis method of the present invention, it was found that when the Mo content in the test sample is ≤0.05%, it will not interfere with the determination of the acid-soluble aluminum content. In this embodiment, the Mo content in the cord steel is generally less than 0.01%; however, when this scheme is used for other samples with Mo content ≥0.05% and acid-soluble aluminum content ≤0.004%, it will produce obvious interference and cause the measured value to be too high.
[0065] According to the above technical scheme, three cord steel samples containing different high, medium and low acid-soluble aluminum were randomly selected for repeatability test. It is difficult for cord steel to contain more than 0.01% acid-soluble aluminum. Therefore, the high point of the curve was verified by the standard sample "Cai Zi 225" (Shanghai Institute of Materials) with a composition similar to that of cord steel. The results are shown in Table 3 below.
[0066] Table 3 Precision of sample analysis results ( n =6)
[0067]
[0068] As can be seen from Table 3, the standard deviation of the cord steel is ≤0.00005, indicating that the sample is evenly processed and the results are representative; the relative standard deviation is ≤3.61%, indicating that the method has good precision.
[0069] Since the market lacks standard samples of acid-soluble aluminum ≤ 0.0010%, in order to verify the accuracy of the low content of the curve, the method of adding standard verification is used for verification. The results are shown in Table 4 below; among them, the upper limit content of the curve can be seen in the sample analysis precision table material word 225 analysis results, and its standard value is 0.040%, which is completely consistent with the analysis value of 0.04017%.
[0070] Table 4 Spiked recovery results
[0071]
[0072] As can be seen from Table 4, the recovery rate of the test sample is 96.0-110.0, indicating that the analysis method of the present invention is accurate and reliable. The method can be used to detect 0.0002%-0.04% acid-soluble aluminum in cord steel, solving the problem of no analysis method for ultra-low acid-soluble aluminum in steel. The method has the characteristics of high accuracy, low analysis cost and no environmental pollution, which is conducive to promotion and application.
[0073] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.
Claims
1. A method for analyzing ultra-low acid-soluble aluminum in cord steel ping-pong samples, characterized in that: The steps include: 1) Annealing the cord steel ping-pong sample, and removing the surface oxide layer after the sample is cooled to obtain a pre-treated sample; wherein the annealing process is: heating the cord steel ping-pong sample in a heating furnace at 800°C to 950°C for 2h to 4h, and removing the surface oxide layer with a thickness of not less than 1mm; 2) Drill the pretreated sample, wash and dry the cuttings in anhydrous ethanol and use them as test samples; 3) Weigh the test sample, first dissolve the test sample with dilute nitric acid until the reaction is stable, then add dilute hydrochloric acid to dissolve the test sample under heating conditions, and then add deionized water intermittently during the dissolution process until the test sample is completely dissolved to obtain a reaction solution; the specific process is: weigh the test sample in a steel volumetric flask, first add dilute nitric acid to it to react for 3-5 minutes, then add dilute hydrochloric acid to mix, and dissolve the test sample under heating conditions of 200°C-300°C; when bubbles appear on the surface of the reaction solution, add deionized water for the first time, continue to heat until bubbles appear on the surface of the reaction solution, add deionized water for the second time, continue to heat until bubbles appear on the surface of the reaction solution, add deionized water for the third time, finally heat until bubbles appear on the surface of the reaction solution and the test sample is completely dissolved, then cool to obtain a reaction solution; 4) Using medium-speed quantitative filter paper to perform hot filtration on the reaction solution, and using acid washing on the filter paper to obtain a test solution containing all the acid-soluble aluminum in the test sample; 5) Prepare a 100µg / mL aluminum standard solution using pure aluminum and hydrochloric acid as reactants; use high-purity iron as a reference component and adopt the same dissolution steps as the test sample to obtain an iron solution; wherein the mass fraction of aluminum in pure aluminum is not less than 99.99%, and the mass fraction of iron in high-purity iron is not less than 99.98%; 6) Using the iron solution as a blank solution, different concentrations of acid-soluble aluminum standard solutions were prepared by adding different volumes of aluminum standard solutions; wherein the volume of aluminum standard solution added to any acid-soluble aluminum standard solution did not exceed 2.00 mL; 7) Using an inductively coupled plasma emission spectrometer, analyze the acid-soluble aluminum standard solution at the analytical line of 396.152 nm under set analysis parameters to obtain an acid-soluble aluminum calibration curve; wherein the correlation coefficient of the acid-soluble aluminum calibration curve is not less than 0.9999; 8) Determine the acid-soluble aluminum content in the test solution based on the acid-soluble aluminum calibration curve.
2. The method for analyzing ultra-low acid-soluble aluminum in cord steel ping-pong samples according to claim 1, characterized in that: The analysis parameters set in step 7) are: RF power 1150 W, nebulizer flow rate 0.50 L / min, pressure 2.10-2.30 bar, auxiliary gas flow rate 0.50 L / min, cooling gas flow rate 12.5 L / min, analysis pump speed 45 rpm, left background subtraction point 396.13 nm, right background subtraction point 396.17 nm.
3. The method for analyzing ultra-low acid-soluble aluminum in cord steel ping-pong samples according to claim 2, characterized in that: The lower limit of detection of the acid-soluble aluminum content by the analytical method at the analytical spectrum line of 396.152 nm is 0.00015%.
4. The method for analyzing ultra-low acid-soluble aluminum in cord steel ping-pong samples according to claim 1, characterized in that: In the step 3), the dilute nitric acid is prepared by mixing nitric acid and deionized water in a volume ratio of 1:1, and the dilute hydrochloric acid is prepared by mixing hydrochloric acid and deionized water in a volume ratio of 1:1, and both nitric acid and hydrochloric acid are selected from reagents of premium purity or above.
5. The method for analyzing ultra-low acid-soluble aluminum in cord steel ping-pong samples according to claim 1, characterized in that: The resistivity of the deionized water is not less than 18 MΩ·cm.
6. The method for analyzing ultra-low acid-soluble aluminum in cord steel ping-pong samples according to claim 1, characterized in that: The mass of the test sample used for the determination of the mass fraction of acid-soluble aluminum in the analytical method is not less than 2.0 g, and the total mass of the test sample used for the repeatability test is not less than 6.0 g.
7. The method for analyzing ultra-low acid-soluble aluminum in cord steel ping-pong samples according to claim 1, characterized in that: The content of acid-soluble aluminum in the cord steel determined by the analytical method is 0.0002%~0.04%.
Citation Information
Patent Citations
Inductively coupled plasma emission spectroscopy analysis method of acid soluble aluminum and acid insoluble aluminum
CN106568764A
Method for accurately measuring content of acid-soluble aluminum in steel
CN117554355A